2004
DOI: 10.1002/chem.200305639
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Ionic Hydrogenations

Abstract: Catalytic ionic hydrogenation of ketones occurs by proton transfer to a ketone from a cationic metal dihydride, followed by hydride transfer from a neutral metal hydride. This contrasts with traditional catalysts for ketone hydrogenation that require binding of the ketone to the metal and subsequent insertion of the ketone into a M-H bond. Ionic hydrogenation catalysts based on the inexpensive metals molybdenum and tungsten have been developed based on mechanistic understanding of the individual steps required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
206
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(211 citation statements)
references
References 62 publications
2
206
0
2
Order By: Relevance
“…Once the aldehyde is generated, the process for the hydrogenation of its C=O bond to an alcohol proceeds through an ionic hydrogenation pathway [22] as reported earlier for a series of molybdenum and tungsten hydrides, with the cationic dihydride or dihydrogen complex serving as the proton source and the neutral hydride being the hydride donor. [23] A series of experiments to be reported separately show that a variety of ketones can be hydrogenated using…”
Section: Mechanism Of the Catalytic Deoxygenation And Hydrogenationmentioning
confidence: 96%
See 1 more Smart Citation
“…Once the aldehyde is generated, the process for the hydrogenation of its C=O bond to an alcohol proceeds through an ionic hydrogenation pathway [22] as reported earlier for a series of molybdenum and tungsten hydrides, with the cationic dihydride or dihydrogen complex serving as the proton source and the neutral hydride being the hydride donor. [23] A series of experiments to be reported separately show that a variety of ketones can be hydrogenated using…”
Section: Mechanism Of the Catalytic Deoxygenation And Hydrogenationmentioning
confidence: 96%
“…Similar reactions were found for ionic hydrogenation of alkenes, [19] a,b-unsaturated ketones, [20] and acyl chlorides, [20] as well as conversion of acetals to ethers. [21] Catalytic ionic hydrogenations [22] were developed using molybdenum and tungsten complexes, in which both the proton as well as the hydride were delivered from a metal hydride bond, with regeneration of the metal hydrides being carried out through reaction with H 2 . [23] These reactivity patterns suggest that deoxygenation of diols might be possible by using acidic and hydridic reactions catalyzed by organometallic complexes.…”
Section: -H )]mentioning
confidence: 99%
“…13 for the hydrogenation with molecular hydrogen catalyzed by the diphosphine-Ru-diamine system (a) and for transfer hydrogenation catalyzed by the (arene)Ru-diamine complex (b) in its simplified representation. Depending on transition-metal catalysts, an ionic mechanism has also been proposed where the proton and hydride transfer occur in separate steps (Bullock, 2004).…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…15, for imine TH, being active at very low loadings. This has been extensively used in reductive amination 35 of ketones including carbohydrates FA/TEA. [200] It was found that the control of the pH (best ca.…”
mentioning
confidence: 99%